Age estimation based on the volume change in the maxillary premolar crown using micro CT. (March 2019) - Asami, Ruri; Aboshi, Hirofumi; Iwawaki, Atsushi; Ohtaka, Yusei; Odaka, Kento; Abe, Shinichi; Saka, Hideki
Highlights: High accuracy estimation is possible by using micro X-ray CT. The method excluding the enamel was an effective index when estimating age. Clarified that maxillary second premolar exhibits stable age-related change. Abstract: Age is often estimated using teeth because numerous external and internal changes appear due to aging. The purpose of this study was to investigate an age estimation method based on the volume ratio of the internal structure of the crown. 61 maxillary first premolars and 50 maxillary second premolars from subjects aged 20–79 years old were used. Micro CT, which can be used to analyze teeth in a non-destructive manner with high sensitivity, was employed in the present study. In consideration of individual differences among subjects, the volume ratio was calculated for the following four items: The pulp chamber was calculated separately based on the presence of enamel. The volume ratio of the enamel to the entire crown: EVR. The volume ratio of the dentin to the entire crown: DVR. The volume ratio of the pulp chamber to the entire crown: PVR (E + ) The volume ratio of the pulp chamber to the entire crown excluding the enamel: PVR (E − ) In order to estimate age, regression analysis was conducted with the actual age as the dependent variable and each volume ratio as the independent variable. As a result, the highest correlation was found with PVR (E − ) for each measurement item. Therefore, the regression equation using the volume change of the maxillary premolar crown as an index was as follows: Age = −12.43 × 4 : PVR (E − ) + 69.85. Age = −12.94 × 5 : PVR (E − ) + 72.54.